Sudu Kecil Enterprise @damira_brownies / Asnidah Salleh, Raja Amir Azrul Shah Raja Azam Shah and Juhaida Salim - Salleh, Asnidah; Raja Azam Shah, Raja Amir Azrul Shah; Salim, Juhaida (2017)
Sudu kecil Enterprise is a start-up bakery establishment located in No 300 Bandar Puncak Alam, Puncak Alam 42300 Shah Alam Selangor. Sudu kecik Enterprise expects to catch the interest of a regular loyal customer base with its broad variety of bakery products especially brownies. Sudu Kecik Enterprise is a new shop that caters to the regular local in Puncak Alam Selangor. As our name suggests, our focus is to provide fresh, unique and high quality bakery product.